Peningkatan Kesadaran Lingkungan dan Pemanfaatan Sampah Organik Melalui Program KKN di Desa Dasan Geria - Hidayat, Nabil Huwaidi; Azizah, Dira Zul; Wahyu, Angie Laluna Mutu; Mansiz, Ahmad Ilhan; Faridsi, Raden Yuwan; Maulida, Siti Sukma; Adelia, Nurul; Andriani, Lisa; Noverisa, Ade Ananda; Rawiana, Shofia (Universitas Mataram, 2025)
This study examines a Community Service Program (Kuliah Kerja Nyata or KKN) implemented in Dasan Geria Village, West Lombok, Indonesia, focusing on enhancing environmental awareness and promoting the utilization of organic waste. The primary objective was to increase community understanding of responsible waste management through socialization activities and demonstrating the production and application of liquid organic fertilizer (POC). The KKN team produced POC from locally sourced organic waste and distributed it to community members, along with plant seedlings and an informative leaflet. The program's impact was evaluated through observations and personal interviews, which indicated heightened awareness of waste management issues among community members. The provision of POC and seedlings encouraged the adoption of sustainable gardening practices. (Desa & Judd, 1995; Fatmawati et al., 2022)